Heterogeneous Agent Models: Two Simple Case Studies - Cars Hommes (Tinbergen Institute, 2005)
These notes review two simple heterogeneous agent models in economics and finance. The first is a cobweb model with rational versus naive agents introduced in Brock and Hommes (1997). The second is an asset pricing model with fundamentalists versus technical traders introduced in Brock and Hommes (1998). Agents are boundedly rational and switch between different trading strategies, based upon an evolutionary fitness measure given by realized past profits. Evolutionary switching creates a nonlinearity in the dynamics. Rational routes to randomness, that is, bifurcation routes to complicated dynamical behaviour occur when agents become more sensitive to differences in evolutionary fitness.
Keywords: B4; C0; C6; D84; E3; G1; G12; 330; interacting agents; complex adaptive systems; evolutionary dynamics; bounded rationality; nonlinear dynamics; bifurcations and chaos.; Chaostheorie; Beschränkte Rationalität; Anpassung; Theorie; Agentenbasierte Modellierung; Soziale Beziehungen; Nichtlineare dynamische Systeme